It is time computers do clever things! The impact of dependent interviewing on interviewer burden - Emanuela Sala; S.C. Noah Uhrig; Peter Lynn (University of Essex, Institute for Social and Economic Research (ISER), 2009)
This paper evaluates the impact of dependent interviewing (DI) on interviewer burden and data quality using qualitative data collected from a survey carried out in 2006 on the British Household Panel Survey (BHPS) interviewers. We find that: (i) DI has a minor effect on interviewer burden, (ii) this effect is perceived by interviewers to be positive, (iii) the mechanisms by which DI reduces interviewer burden are mainly indirect as they are mediated by respondents, and (iv) in most cases the effects of DI on interviewer burden varies in relation to the type of DI questions asked and respondent circumstances.
Keywords: 330